Reciprocity at any cost? - Ng, Siew Imm; Lau, Yeng Wai; Ho, Jo Ann (Universiti Putra Malaysia Press, 2009)
This case on business culture in Malaysia presents an opportunity for post-graduate and final year undergraduate students the exposure on relationship-marketing, cultural value dimensions, reciprocity as well as ethical issues. The case was about a breach of verbal trust given to a client who resulted in the focal company facing the risk of losing significant amount of time and financial losses. This case has a moderate level of difficulty and may be used to teach marketing, crosscultural management and business ethics.